Versatile roles of lipids and carotenoids in membranes - Domonkos, Ildikó; Kis, Mihály; Gombos, Zoltán (Acta Biologica Szegediensis, 2015)
Chemical characteristics and functions of constitutive membrane lipids, fatty acids and carotenoids, are summarized. Lipids and carotenoids are major components of biological membranes, and perform several important physiological and structural functions in all kingdoms of living organisms. Structural lipids build up and maintain the architecture of biological membrane, while active lipids originating from membranes have signaling functions. Unsaturated lipids protect photosynthetic organisms against low-temperature photoinhibition and keep necessary membrane microviscosity under various environmental conditions. Sterols are capable of controlling membrane order and segregation of lipids into rafts by intercalating between phospholipids. Carotenoids are essential structural and functional components of photosynthetic complexes and membranes in plants, algae and cyanobacteria. They have a role in light harvesting processes and the elimination of excitation energy. They can serve as protectant agents against reactive oxygen and nitrogen species. Heat dissipation is involved in protective processes. Carotenoids are effective quenchers and scavengers of singlet oxygen and other free radicals, therefore they suppress lipid peroxidation and other harmful biochemical reactions. Carotenoids are indispensable antioxidants in photosynthetic organisms and also in animals, which are not capable of synthesizing them. Both carotenoids and essential lipid species are necessary for human diet.